Financial and Economic Stability of Railway Sector in the Context of Globalization and Integration - Steshenko, Olena; Masalygina, Viktoriia; Salenko, Olena (International Journal of Engineering and Technology, 2018)
This paper is dedicated to the study of financial and economic security of the railway sector in the context of globalization and integration through the example of PJSC Ukrzaliznytsia. The study covers theoretical and methodological approaches to identification of criterion for assessment of financial and economic security of the railway sector.It provides the proof of the increasing competition, diversity of internal and external risks and uncertainty in conditions of contemporary integration processes. The paper offers the cause-and-effect analysis through the â€œTree of Problemsâ€. Key indicators of financial and economic security of the railway enterprises are singled out of the overall system of threats (risks). Each indicator is assessed for impact on the overall value of the Pareto-efficient integral risk and the equation for calculation of the integrated risk value is formulated.Findings of the study confirm that monitoring of the existing and potential threats determines the operating and prognostic goals of functioning of the financial and economic security, which allows to formulate the relevant mechanisms and tools for the attainment thereof.Â Â